Synergistic enhancement of antioxidant and antiapoptotic levels by Vitamin A and Lupeol improves the quality of cryopreserved bucks semen - Wang, Congliang; Yun, Xiayu; Song, Yanfeng; Ju, Minying; Wang, Meixia; Song, Xiaoyue; Li, Helin; Li, Na; Qu, Lei; Hua, Jinlian; Du, Xiaomin; Zhu, Haijing (Frontiers in Veterinary Science, 2026)
This study investigated the effects of supplementing bucks semen extenders with Vitamin A (Vit A) and Lupeol (Lup) on post-thawing quality. Pooled semen from six bucks was cryopreserved using extenders containing varying concentrations of Vit A and Lup. Post-thawing assessments included sperm kinematic parameters, plasma membrane and acrosome integrity, antioxidant enzyme activities, and the expression of antioxidant and apoptosis related genes. The results showed that the addition of 0.75 μM Vit A significantly improved post-thaw sperm motility, kinematic velocities (VSL, VCL, VAP), membrane integrity, and acrosome integrity compared to the control. Compared with the control group, this group also exhibited the significantly improved activities of SOD, CAT, and GSH-Px, along with significantly upregulated expression of the antioxidant genes SOD1 and NRF2. Based on these findings, we further evaluated Lup. Compared with the control group, the addition of 2 μM Lup significantly enhanced sperm motility, VSL, WOB, and antioxidant enzyme activity. It also increased the expression of SOD1, NRF2, GPX4, and CAT, while reducing the transcriptional levels of the apoptotic genes Caspase 3 and P53. Furthermore, compared to fresh semen, frozen semen supplemented with 0.75 μM Vit A and 2 μM Lup exhibited good fertilization capacity, although no significant differences were observed in cleavage rate or blastocyst rate. In conclusion, Vit A and Lup act synergistically in bucks semen cryopreservation. They enhance antioxidant capacity, suppress apoptosis-related gene expression, and mitigate oxidative stress during freeze-thawing, thereby improving semen quality.